Task Complexity: Extending a Core Concept - Hærem, Thorvald; Pentland, Brian T.; Miller, Kent D. (Academy of Management Review, 2015)
We reexamine the assumptions of current theory to update and extend the concept of task complexity to tasks that include multiple actors at any level of analysis. Tasks can be modeled as networks of required actions and information cues carried out or processed by particular actors. Counting pathways in the task network provides an index of task complexity that incorporates insights from organization research but is more consistent with contemporary complexity science than prior approaches and better reflects the exponential nature of the phenomenon. The revised concept of task complexity can be readily used as an independent or dependent variable, and it can be used to compare observed and idealized descriptions of tasks. We discuss its implications for developing theory.